2023
DOI: 10.2478/logi-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Number of Road Accidents in Poland Depending on the Day of the Week using Neural Networks

Abstract: The number of road accidents in the world is decreasing year by year. This number has been affected by the pandemic in recent years but is still very high. Therefore, it is necessary to take all possible measures and steps to reduce this number. The objective of the article is to forecast the number of road accidents in Poland depending on the day of the week. For this purpose, the annual data on the number of road accidents in Poland broken down by days of the week were analyzed, and a forecast for the years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The purpose of using dummies in crash experiments is to reduce the number of deaths caused by traffic accidents [33,34,35]. The topic of traffic accidents is discussed in articles [36,37,38,39]. It should be noted that thanks to dummies, it is possible to predict the likelihood of people being injured in a road accident [40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of using dummies in crash experiments is to reduce the number of deaths caused by traffic accidents [33,34,35]. The topic of traffic accidents is discussed in articles [36,37,38,39]. It should be noted that thanks to dummies, it is possible to predict the likelihood of people being injured in a road accident [40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Selected time series models and exponential models were used to forecast the number of accidents. Forecasting of the number of road accidents using factors influencing this value and the use of other forecasting methods (e.g., neural networks, linear regression) can be found in the author's other work in this area [49][50][51][52][53][54][55][56][57][58][59][60][61]. In their study, the authors used the police's statics data, not taking into account other factors affecting the occurrence of a traffic accident.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of their study was to increase traffic fluency, safety, and environmental protection in urban areas. Neural networks has also been used in a study to forecast the number of road accidents and the authors opined that neural networks are an effective tool to study traffic scenarios [30]. In a dated study [31], the authors reviewed and suggested various traffic scenarios/contexts, which should be studied in detail; and one of them was to address the travel time by various categories of vehicles.…”
Section: Introductionmentioning
confidence: 99%